Applied research of shaking table for scandium concentration from a silicate ore. (March 2018) - Yan, P; Zhang, G F; Gao, L; Shi, B H; Shi, Z; Yang, Y D
Abstract: A poor magnetite iron ore is a super large independent scandium deposit with over the multi-billion potential utilizable value. Shaking table separation is very useful for impurities removing and scandium content increasing as a follow-up step of high-intensity magnetic separation. In the present study, a satisfactory index, namely scandium content of 83.10 g/t and recovery rate of 79.45 wt%, was obtained by shaking table separation. The good result was achieved under the conditions which the parameters were feed concentrate of 18 wt%, feeding quantity of 11 L/min, stroke frequency of 275 times/min and stroke of 17mm.